¿El virus afecta “a todos (y a todas) por igual”? Una mirada crítica acerca del trabajo doméstico remunerado en Argentina en tiempos de pandemia por COVID-19 - Casas, Verónica; Palermo, Hernán (El Colegio de México A.C., 2021)
This paper analyzes the impact of the COVID-19 pandemic on the paid domestic employment sector in Argentina. Our methodological approach triangulates quantitative and qualitative data through an online survey and by conducting online interviews with women employed in private homes. Our finding was that the pandemic situation exacerbated this sector’s characteristic structural precariousness. Furthermore, pandemic discourses structured around the production of the signifiers of masculinity further devalued this work from a social perspective, in contrast to the “naturally” feminine signifiers associated with domestic work.